Report of epibiont ciliates (Cilliophora: Suctorea) on pelagic ostracods (Crustacea: Ostracoda) from the Arabian Sea - Chatterjee, Tapas; Dovgal, Igor; Nanajkar, Mandar; Fernandes, Veronica (Zootaxa, 2019)
The article deals with the report of 5 suctorians viz. Lecanophryella satyanandani (Santhakumari, 1986), Paracineta karunakarani Santhakumari, 1986, Ephelota gemmipara (Hertwig, 1876), Acineta foetida Maupas, 1881 and Pelagacineta sp. on marine pelagic ostracods Cypridina dentata (Müller, 1906) from new localities of the Arabian Sea. Diagnostic characters of Paracineta karunakarani are emended. Ephelota gemmipara (Hertwig, 1876) and Acineta foetida Maupas, 1881 are reported here for the first time on planktonic marine ostracods. Pelagacineta sp. is reported for the first time as epibiont on ostracods and from the Indian Ocean.